2014
DOI: 10.1186/1471-2334-14-503
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin rs1617640 G allele associates with an attenuated rise of serum erythropoietin and a marked decline of hemoglobin in hepatitis C patients undergoing antiviral therapy

Abstract: BackgroundA decline in hemoglobin (Hb) concentration during antiviral therapy in chronic hepatitis C (CHC) is a serious side effect. It may compel to dose reduction or even termination of antiviral treatment. The activation of erythropoietin (EPO) synthesis as a physiological response to anemia and its relation to a genetic variation within the EPO gene has not been evaluated yet.MethodsData of 348 CHC patients were reviewed retrospectively. Samples were genotyped for EPO rs1617640 and inosine triphosphatase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
(48 reference statements)
2
6
0
Order By: Relevance
“…78 On the basis of our meta-analysis, each copy of the A-allele at rs1617640 was associated with 0.063 standard deviations (SD), equivalent to 0.32 IU/L, higher endogenous EPO levels (p ¼ 9.32 3 10 À4 ) (Table 1). The effect of the cis-EPO variant is consistent with that previously reported in affected individuals with diabetic retinopathy or hepatitis C. 78,79 The cis-EPO SNP is associated with altered EPO expression and nearby TFR2 expression in the liver To provide additional insight into the rs1617640-EPO association and further evaluate its utility as an instrument, we tested the association of the cis-EPO SNP with gene expression in the kidney and the liver as EPO is highly expressed in these two tissues. 80 In the liver, we found that the C allele at rs1617640 was associated with higher EPO expression (b ¼ 0.22 [0.14, 0.3], p ¼ 6.86 3 10 À8 ) and also TFR2 expression (b ¼ 0.23 [0.17, 0.29], p ¼ 1.56 3 10 À13 ), a gene that lies upstream of the EPO gene and is involved in iron metabolism (Table S3).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…78 On the basis of our meta-analysis, each copy of the A-allele at rs1617640 was associated with 0.063 standard deviations (SD), equivalent to 0.32 IU/L, higher endogenous EPO levels (p ¼ 9.32 3 10 À4 ) (Table 1). The effect of the cis-EPO variant is consistent with that previously reported in affected individuals with diabetic retinopathy or hepatitis C. 78,79 The cis-EPO SNP is associated with altered EPO expression and nearby TFR2 expression in the liver To provide additional insight into the rs1617640-EPO association and further evaluate its utility as an instrument, we tested the association of the cis-EPO SNP with gene expression in the kidney and the liver as EPO is highly expressed in these two tissues. 80 In the liver, we found that the C allele at rs1617640 was associated with higher EPO expression (b ¼ 0.22 [0.14, 0.3], p ¼ 6.86 3 10 À8 ) and also TFR2 expression (b ¼ 0.23 [0.17, 0.29], p ¼ 1.56 3 10 À13 ), a gene that lies upstream of the EPO gene and is involved in iron metabolism (Table S3).…”
Section: Resultssupporting
confidence: 89%
“…Previous associations have been reported between variants near EPO and circulating EPO levels. 78,79 A cis-SNP, rs1617640, lying in the EPO promoter region, 1,125 bp upstream of the transcription start site, was associated with EPO levels in our study and in the previous study. 78 On the basis of our meta-analysis, each copy of the A-allele at rs1617640 was associated with 0.063 standard deviations (SD), equivalent to 0.32 IU/L, higher endogenous EPO levels (p ¼ 9.32 3 10 À4 ) (Table 1).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…These two organs play a major role in erythropoiesis by producing hepcidin and erythropoietin respectively (Ganz and Nemeth, 2012;Amanzada et al, 2011;Beverborg et al, 2015). Inefficiencies of these organs will be key to anemia development.…”
Section: Introductionmentioning
confidence: 99%
“…rs1617640 G > T polymorphism in the EPO gene promoter increases EPO expression in mRNA and consequently protein level. Various studies investigated the association of this polymorphism with diabetes in different populations worldwide (1,(9)(10)(11). In this study we investigated the existence of rs1617640 EPO gene polymorphism among 150 healthy individuals and 150 individuals with diabetes type II who referred to Yazd (an Iranian province) central laboratory.…”
Section: Introductionmentioning
confidence: 99%